Peranan Gaya Kepemimpinan Penatua Gereja terhadap Kinerja Muda-Mudi Gereja Protestan Persekutuan (GPP) Mengikuti Ibadah Raya dan Partangingan (Studi Kasus : Gereja GPP Sukadono Helvetia) - A.M.Hatuaon Sihite (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Large organisations have many different interests, so there is often a lack of understanding of tasks and missions. This study identified several issues, including the impact of current elder performance in GPP Sukadono Helvetia, the condition of elder support that does not meet performance standards, the influence of management on performance, and the impact of elder workload on performance became the main focus of this study. This research is descriptive-inferential, where there are functional relationships. If leadership (X) is systematically related to employee performance (Y), then future phenomena are likely to be predicted and the results may propose new or additional hypotheses that can be tested. This study wants to reveal that there is a significant contribution between leadership effectiveness (X) and employee performance (Y), to the empirical contribution of 27.3%. This shows that leadership plays an important role in overcoming all challenges in the organisation. Elder leadership plays an important role of 27.3% in the performance of GPP Sukadono Helvetia. Then, this study also found that the role of management in this area has not been optimal, resulting in ineffectiveness in achieving the desired performance, especially in promoting learning and improving congregational performance. This study suggests that the role of management in the future should be more aligned with the management and effectiveness of GPP Sukadono Helvetia. This will ensure that the work of GPP Sukadono Helvetia elders is not only focussed on programme activities but also that the programme contributes to the overall success of the organisation.